Effects of supplementing corn silage with MGA and feeding varying levels of sorghum grain to feed-lot heifers - L.I. Smart; C.L. Drake (Kansas Agricultural Experiment Station Research Reports, 1968)
Melengestrol acetate (MGA) 1S a new drug recently approved for use in the supplement portion of rations of feed-lot heifers. The recommended level is from 0.25 to 0.50 mg. per head per day. A 48-hour withdrawal period is required before slaughter. Several experiment stations have shown improved rate of gain, feed utilization and suppressed estrus in feed-lot heifers on high concentrate rations plus MGA.
Keywords: Cattlemen' s Day; 1968; Report of progress (Kansas State University. Agricultural Experiment Station); 518; Beef; Corn silage; MGA; Sorghum grain; Feedlot heifers